Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)

Effects of aqueous extracts from Quercus ilex l. root bark, Punica granatum l. fruit peel and Artemisia herba-alba Asso leaves on ethanol-induced gastric damage in rats (Phytotherapy Research, 1999)
The gastroprotective effect of tannic acid and the aqueous extract of Quercus ilex L. root bark, Punica granatum L. fruit peel and Artemisia herba-alba Asso leaves was investigated in the rat against ethanol-induced damage. Tannic acid, Q. ilex and P. granatum extracts gave 100% precipitation of ovine haemoglobin in vitro, whereas A. herba-alba extract was devoid of any protein-binding property. Oral administration of these plant extracts or tannic acid induced a significant decrease in gastric lesions (47.7%–76%). The observed protection was more pronounced when the test solution was given at the same time with ethanol, except for Q. ilex extract. The acid content of the stomach was significantly increased by P. granatum (368%) and A. herba-alba (251%) extracts prepared in ethanol. It is suggested that monomeric and polymeric polyphenols can strengthen the gastric mucosal barrier. Copyright © 1999 John Wiley & Sons, Ltd.